Paranoid Ideation And Anxiety As Correlates of Domestic Violence Among Married Police Officers - Chine, Bernard C; Ifedigbo, Chinenye F; Onyejiaka, Cynthia (Practicum Psychologia, 2018)
All over the world, domestic violence is an issue of optimum concern, which has been associated with a lot of factors. This paper investigated paranoid ideation and anxiety as correlates of domestic violence among married police officers. Frustration-aggressiondisplacement theory seems to capture the most probable explanation on the correlation between paranoid ideation, anxiety and domestic violence. A total number of 124 married people police officers conveniently selected from Police stations in Amawbia and Awka participated in the study. Their ages ranged between 28 to 56 with the mean age of 28.94 and standard deviation of 5.28. The Symptoms Distress Checklist (SCL-90) by Derogatis, Lipman and Covi (1973), and Conflict Tactics Scale (CTS) by Hertz and Sitterle (2006) were used for data collection. The result of the Pearson Moment Correlation Analysis very strongly suggested that paranoid ideation and anxiety correlated with domestic violence. The researchers recommended that psychological screening as with other health-based screening be conducted on the intending couples before they are joined together.